General Event Planner - Njwan, Fatimah; darawsheh, Bisan (My University, 2017)
Randomization and lack of planning are one of the most important reasons that lead to increased anxiety and stress on the person, which in turn leads to failure in many of daily life tasks and sometimes important events. Moreover, with this evolution and the speed of time that is difficult to keep up with the process of planning has become almost impossible. On the other hand, the propagation of smart phones and their frequent use in everyday life is a good step in facilitating this process. From this point, General event planner was decided to be developed in order to achieve a fundamental point which is how to spend time accomplishing tasks rather than remembering what they are and worrying about them. General event planner is a web and android based application that will perfectly help in managing events by combining many features such as: create events, edit/delete events, pass created events to friends view, filter events by: type(education, IT, social), date, interested in events and created events, show graphs about the percentage of incoming female and male friends and their number in order to improve events behavior, send response to event owner to represent a reply such as (will come, can't, interested), search for friends, add/delete friends, accept/delete friends requests, chat with a friend, check weather conditions based on the location to pick a suitable date for the event, enable/disable showing location to friends, to-do list that keep tracking of user daily tasks and he can set reminder for these tasks, notification system based on the location that will notify the event owner if he is near the event location to enable creator to book the place before the event l